PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi pada Bank Jateng Cabang Koordinator Semarang) - Wahyuningtyas, Nadya; Suharnomo, Suharnomo (Faculty of Economics and Business Diponegoro University, 2013)
Human resources play an important role in a company since human is the power and determiner of the organization. One of the efforts to improve the performance of employees of which having regard to the working environment. Beside that, the other factors to influences of working environment is satisfaction of compensation. Based on Supervisor Research, Coordinator Branch of Jateng Bank Semarang have lowering in employee’s performance.This research was conducted in Coordinator Branch of Jateng Bank Semarang. The goal of this researchis to determine the effect ofworking environment and satisfaction of compensation given toward employee’s performance. The working environment and satisfaction of compensation are the independent variables on this research, whereas the employee’s performance played as the dependent variable.The population of the study was the 78 employees of Coordinator Branch of Jateng Bank Semarang. Census study was used as the sampling techniqueon this research. The data were analyzed by multiple linear regression analysis method supported by SPSS program.This research shows that working environment significantly influences the performance of employees in Coordinator Branch of Jateng Bank Semarang and in positive direction. The compensation also gives a significant influence to the employee’s performance and in positive direction.